Evaluation of Seasonal Heat Stress on Transcriptomic Profiles and Global DNA Methylation of Bovine Oocytes - Diaz, Fabian A; Gutierrez-Castillo, Emilio J; Foster, Brittany A; Hardin, Paige T; Bondioli, Kenneth R; Jiang, Zongliang (Frontiers in Genetics, 2021)
Heat stress affects oocyte developmental competence and is a major cause of reduced fertility in heat stressed cattle. Negative effects of heat stress on the oocyte have been observed at morphological, biochemical and developmental levels. However, the mechanisms by which heat stress affects the oocyte at the transcriptional and epigenetic levels remain to be further elucidated. Here we aimed to investigate the effect of heat stress on oocyte quality, transcriptomic profiles and DNA methylation of oocytes collected through the transition from spring to summer under Louisiana conditions. Summer season resulted in a lower number of high quality oocytes obtained compared to the spring season. There was no difference in in vitro maturation rates of oocytes collected during spring as compared to summer. RNA sequencing analysis showed that a total of 211 and 92 genes were differentially expressed as a result of heat stress in GV and MII oocytes, respectively. Five common genes (E2F8, GATAD2B, BHLHE41, FBXO44, and RAB39B) were significantly affected by heat in both GV and MII oocytes. A number of pathways were also influenced by heat stress including glucocorticoid biosynthesis, apoptosis signaling, and HIPPO signaling in GV oocytes, and Oct4 pluripotency, Wnt/beta-catenin signaling, and melatonin degradation I in MII oocytes. In addition, fluorescent immunocytochemistry analysis showed no difference in global levels of DNA methylation and DNA hydroxymethylation at either the GV or MII stage between spring and summer oocytes. The results of this study contribute to a better understanding of the effect of heat stress on the molecular mechanisms altered in bovine oocytes.